2009
DOI: 10.2298/jas0903179d
|View full text |Cite
|
Sign up to set email alerts
|

Types of interactions in intercropping of maize and soya bean

Abstract: Intercropping two or more crops under similar micro environmental conditions can increase the agricultural productivity. A field study was conducted in three-year period 2003-2005 at experimental field of Maize Research Institute, Belgrade on chernozem soil type. This examination included three experimental hybrids of maize from various FAO groups of ripening (500,600 and 700) and the type of soya bean from II group of ripening (Nena). Maize and soybean was grown in pure stands and three combinations of interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Conventional intercropping field layout often resulted in low LUE, RUE, low comparative profits of soybeans and incompatibility with mechanization (Lv et al, 2014;Yang et al, 2014). Moreover, farmers had no suitable high yield variety for intercropping and always used manpower to manage (Dolijanović et al, 2009) China (traditional): Intercrop yields were adjusted to whole plot basis. Democratic Republic of the Congo: Maize sole crop yield was calculated from gross income and maize unit price (300 CDF/kg).…”
Section: Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional intercropping field layout often resulted in low LUE, RUE, low comparative profits of soybeans and incompatibility with mechanization (Lv et al, 2014;Yang et al, 2014). Moreover, farmers had no suitable high yield variety for intercropping and always used manpower to manage (Dolijanović et al, 2009) China (traditional): Intercrop yields were adjusted to whole plot basis. Democratic Republic of the Congo: Maize sole crop yield was calculated from gross income and maize unit price (300 CDF/kg).…”
Section: Chinamentioning
confidence: 99%
“…As maizesoybean intercropping has a potential to increase the soil fertility, LER, yield per unit land area and net return in world farming system. Therefore, several researchers other than above-mentioned countries have also indicated the significance of this system (Dolijanović et al, 2009;Duùa & Roman, 2013;Polthanee & Trelo-Ges, 2003). However, this system is adopted on small scales because many modifications and alterations are needed to be considered, for example, row arrangements, light and nutrients availability, inter-and intra-specific competition and mechanization.…”
Section: Questions and Implications Of Maize Soybean Intercropping Symentioning
confidence: 99%
“…Intercropping consists of simultaneous culture of two or more crops in the same field in order to reach land equivalent ratios that show nature prefers multiple species rather than single species [1], [2]. It has been traditionally practiced in many parts of the world [3], [4] and has some advantages over monocultures [4].…”
Section: Introductionmentioning
confidence: 99%
“…The tall nature of maize in relation to soybean and its more widespread rooting system might have favored maize in D1. Dolijanović, Kovačević, Oljača, and Simić (2009) showed that, in the intercrops of soybean and maize, the maize component, which has often fast growth rate, height advantage and more widespread rooting system gives it an advantage in the competition with the associated soybean. The observed consistent, but slight increase in maize yield under D1, relative to SM in the long rainy season, may be due to N obtained through nitrogen fixation from associated soybean.…”
Section: Soybean and Maize Grain Yieldmentioning
confidence: 99%